Analgetik Power Test Of Herba Katuk (Sauropus androgynus) Ethanol Extract On Mice (Mus musculus) With Acetic Acid Induction: UJI EFEKTIVITAS ANALGETIK EKSTRAK ETANOL HERBA KATUK (Sauropus androgynus) PADA MENCIT PUTIH (Mus musculus) DI INDUKSI ASAM ASETAT - Nur Meina Anjeli; Nur Mahdi; Ani Agustina (Jurnal Ilmiah Kesehatan, 2022)
. Indonesia is a country with an abundance of potential natural resources. Herbaceous plants, which are found in forests and are smaller than trees or shrubs, have moist stems, and are not woody, are one type of plant utilized in traditional medicine. Katuk is a herbaceous plant that belongs to the Euphorbiaceae family. This study aims to examine the analgesic effectiveness of katuk herb (Sauropus androgynus) in mice (Mus musculus) compared to diclofenac sodium. The method used for the analgesic test is the stretching method. Twenty-five mice were separated into five groups, each with five mice in a row, namely positive control (diclofenac sodium), negative control (Na-CMC 0,5%), dose 1 (8.4 mg/20 g BW), dose 2 (11.2 mg/20 g BW), and dose 3 (14 mg/20 g BW). Each group was administered the test material orally, then 1 percent acetic acid intraperitoneally 30 minutes later, and the number of stretches was counted every 15 minutes for 90 minutes. The results obtained were analyzed using one way ANOVA test. The test results revealed that the higher the dose of katuk herbs given, the better the analgesic effect. Based on the ANOVA test and LSD test, katuk herb at dose 3 had a higher effectiveness than the positive control and the treatment group at dose 1, and dose 2.